Presenting an innovative single-setting adaptive protection method for AC microgrid with wind turbine - Jahanbani, Hassan; Razavi, Farzad; Nafisi, Hamed (Electrical engineering, 2025)
Today, despite numerous studies which have been conducted on the subject of adaptive protection, there are still many shortcomings in this field. For example, the presence of a wind turbine in the network changes the short-circuit currents value and might result in the malfunction of overcurrent relays. In addition, changes in the microgrid topology will create many protection settings, which will create problems for saving the settings or changing them. For this reason, in this paper, a new adaptive protection method based adaptive linear prediction, whale optimization algorithm is proposed. In this method, first, the overcurrent protection relay is replaced by an algorithm based on adaptive linear prediction for fault detection, and then a single setting required by this method is pre-calculated in different microgrid conditions and topologies and updated using a central protection system. The proposed method is tested in different microgrid topologies and under different fault conditions. The results prove the efficiency and the superiority of the proposed method over existing adaptive protection methods.